The Long-Term Effect of Medically Enhancing Melanin Intrinsic Bioenergetics Capacity in Prematurity - Herrera, Arturo S.; Solís Arias, Paola E.; del C.A. Esparza, María; Bernal, Luis F.T.; Bondarev, Andrey D.; Fisenko, Vladimir P.; Chubarev, Vladimir N.; Minyaeva, Nina N.; Mikhaleva, Liudmila M.; Tarasov, Vadim V.; Somasundaram, Siva G.; Kirkland, Cecil E.; et al. (Current Genomics, 2020)
Background: The ability of the human body to produce metabolic energy from light modifies fundamental concepts of biochemistry. Objective: This review discusses the relationships between the long-accepted concept is that glucose has a unique dual role as an energy source and as the main source of carbon chains that are precursors of all organic matter. The capability of melanin to produce energy challenges this premise. Methods: The prevalent biochemical concept, therefore, needs to be adjusted to incorporate a newly discovered state of Nature based on melanin’s ability to dissociate water to produce energy and to reform water from molecular hydrogen and oxygen. Results and Discussion: Our findings regarding the potential implication of QIAPI-1 as a melanin precursor that has bioenergetics capabilities. Conclusion: Specifically, we reported its promising application as a means for treating retinopathy of prematurity (ROP). The instant report focuses on the long-term treatment medical effects of melanin in treating ROP.
Keywords: hydrogen